EVALUATION OF EFFECTIVENESS OF SPLENECTOMY IN CHRONIC LEUKEMIAS - Ergashev Ulugbek Yusufjanovich; Mustafakulov Gaybulla Irisbaevich; Zokhirov Adkhamjon Rafiqovich; Abdusalomov Behzod Alisher ugli; Ernazarov Khojimurod Irsaliyevich (Scholar Express Journals, 2023)
This work presents observation data for 16 patients with hairy cell leukemia (HCL), the duration of the disease ranged from 1 to 15 years. The indications for surgery in case of ON and the results of splenectomy in 5 patients are presented. No complications from operations were observed. After splenectomy, the patients' condition improved platelets, blood retraction normalized, hemoglobin and erythrocytes rose in dynamics, hemorrhagic syndrome disappeared, hemodynamics stabilized. Despite the positive clinical and laboratory effect after splenectomy for a year, the further prognosis of the disease remains serious and patients need constant dispensary observation.
Keywords: hairy cell leukemia; complications; splenectomy; results